Productivity, nutrient uptake and soil fertility as influenced by phosphorus management in pigeonpea (Cajanus cajan)-wheat (Triticum oesiivum) cropping system - SINGH, UMMED; AHLAWAT, I P S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted at New Delhi during 2002-04 on sandy loam soil low in available P to study the efficient management of phosphorus in pigeonpea [Cajanus cajan (L.) Millsp.1-wheat (Triricum aestinlwl L. emend. Fiori & Paol.) cropping sytem. Application of P up to 17.2 kgha applied to pigeonpea significantly enhanced the grain (2.06 tonnesiha) and stover yield (8.35 tonnesiha) ofpigeonpea, and grain (4.56 tonnesiha) and straw yield (6.59 tonneska) of succeeding wheat over no P and phosphate solubilizing bacteria. Direct application of P to wheat up to 17.2 kglha along with phosphate solubilizing bacteria recorded higher grain (4.85 tonneslha) and straw yield (7.04 tonnesha) of wheat over their lower levels. Application of 17.2 kg Plha + phosphate solubilizing bacteria to both pigeopea and wheat recorded higher wheat yield (4.89 tonneslha) and total productivity (4.59 tonnesiha) in terms of pigeonpea equivalent yield. Application of 34.4 kg Pha to pigeonpea, being on a par with 17.2 kg Pha + phosphate solubilizing bacteria, recorded higher N (1 88.3 kgiha) uptake in pigeonpea, and succeeding wheat (104.6 kg N) over lower rates of P, whereas the maximum P uptake in pigeonpea (13.4 kgiha) and wheat (14.3 kgiha) was recorded with 34.4 kg Plha. Further, direct application of P to wheat at 34.4 kg Plha recorded higher N (1 10.9 kglha) and P (2819 kgiha) uptake by wheat over the lower levels. Negative balance of soil availableN was noticed in plots fertilized with 17.2 kg P/ha+ phosphate solubilizing bacteria and 34.4 kg Pha after pigeonpea as well as wheat harvest. However, the status of available soil P improved with the increase in applied P both in pigeonpea and wheat. Both pigeonpea and wheat receiving 17.2 kg Piha with phosphate solubilizing bacteria improved the bacterial count in soil rhizosphere over lower levels at harvest of these crops.